Minimally Invasive Left Ventricular Assist Device Implantation: A Comparative Study. Issue 12 (15th November 2018) - Mohite, Prashant N.; Sabashnikov, Anton; Raj, Binu; Hards, Rachel; Edwards, Gemma; García‐Sáez, Diana; Zych, Bartlomiej; Husain, Mubassher; Jothidasan, Anand; Fatullayev, Javid; Zeriouh, Mohamed; Weymann, Alexander; et al.
Abstract: Left ventricular assist device (LVAD) is now a routine therapy for advanced heart failure. Minimally invasive approach via thoracotomy for LVAD implantation is getting popular due to its potential advantage over the conventional sternotomy approach in terms of reduced risk at re‐operation due to sternal sparing. We compared the approaches (thoracotomy and sternotomy) to determine the superiority. Minimally invasive approach involved fitting of the LVAD inflow cannula into left ventricle apex via left anterior thoracotomy and anastomosis of outflow graft to ascending aorta via right anterior thoracotomy. In the sternotomy approach, both the procedures were performed via sternotomy. Outcomes in patients after LVAD implantation were compared depending on these approaches for the surgery. Two hundred and five continuous flow LVAD implantations performed between July 2006 and June 2015 at a single center were divided based on surgical approach, that is, sternotomy ( n = 180) and thoracotomy ( n = 25) groups. There was no significant difference between the groups in relation to patient demographics, preoperative hemodynamic parameters, laboratory markers, or risk factors. There was no significant difference between the groups in terms of postoperative hemodynamic parameters, laboratory markers, bleeding and requirement of blood products, intensive care unit, and hospital stay or complications of LVAD surgery. There were no significant differences in terms of long‐term survival (Log‐Rank P = 0.953), however, thoracotomy, compared to sternotomy approach, incurred significantly less requirement of temporary right ventricular assist (4 vs. 19.4%, P = 0.041). Minimally invasive bilateral thoracotomy approach for LVAD implantation in addition to benefits of sternal sparing avoids dilatation of right ventricle and reduces chances of right ventricular failure requiring temporary right ventricular assist.